Analisis Kualitas Pelayanan Elektronik (E-SERVQUAL): Berfokus pada Website ZuBlu - Ayu Sri Maharani, Ajeng; I Putu Agus Swastika; Ni Luh Putu Ning Septyarini Putri Astawa (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2023)
This research was conducted to determine the level of electronic service quality owned by ZuBlu using 7 dimensions of e-ServQual. Measurement of service quality is carried out by calculating the gap between the expected service and the service received by the customer. The main data were collected using a questionnaire that had passed normality, validity, and reliability tests using Statistical Program for Social Science (SPSS) software. The questionnaire was filled out by respondents who had used and transacted through the ZuBlu website with a non-probability accidental sampling technique of 100 respondents. From the results of research conducted, it can be concluded that the service quality that exceeds user expectations is on the dimensions of responsiveness and contact, while the service quality that adequately meets user expectations is in 3 dimensions, namely fulfillment, privacy, and compensation, then the service quality that is still lacking contained in dimension of efficiency and system availability.